2018
DOI: 10.1172/jci.insight.121510
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose beiging in response to cold and mirabegron

Abstract: NIH (DK107646, DK112282, P20GM103527, and by CTSA grant UL1TR001998).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
184
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(196 citation statements)
references
References 61 publications
7
184
5
Order By: Relevance
“…Lipolysis is often triggered by fasting, exercise, and cold exposure, which mobilize the stored excessive energy for coping with increased metabolic rates. As a β3adrenoreceptor agonist, mirabegron has been shown in humans to be able to activate BAT and thermogenesis (31,32). In this work, we show that a clinical relevant dose of mirabegron can activate BAT and induce a browning phenotype in subWAT and visWAT in mice.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Lipolysis is often triggered by fasting, exercise, and cold exposure, which mobilize the stored excessive energy for coping with increased metabolic rates. As a β3adrenoreceptor agonist, mirabegron has been shown in humans to be able to activate BAT and thermogenesis (31,32). In this work, we show that a clinical relevant dose of mirabegron can activate BAT and induce a browning phenotype in subWAT and visWAT in mice.…”
Section: Discussionmentioning
confidence: 51%
“…More recently, a causal link between anticholinergic burden and the development of dementia has been established (28)(29)(30), raising further concerns about the safety issue in human patients. Activation of the β3-adrenergic receptor also induces BAT activation and browning of WAT (31,32). In a recent pilot human study, it has been shown that a clinical dose of mirabegron can activate BAT and browning WAT in human subjects (32).…”
Section: Significancementioning
confidence: 99%
“…We were also able to elucidate the impact of sympathetic activation in the absence of any change in housing temperature by administering YM-178. This highly selective β3-agonist increases BAT activity, whole body EE and induces ‘browning’ in humans [28-31]. Administration of YM-178 to mice for 4-6 weeks at similar dosage to this study (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, mitochondria from human abdominal subcutaneous WAT following cold exposure showed increased uncoupled and maximal respiration (Kern et al, ). There also appears to be a seasonal variation in UCP1 content in human subcutaneous WAT (Finlin et al, ; Kern et al, ), which also occurs in human adult BAT. Hence, there is some evidence of β‐adrenoceptor function in human brite adipocytes, but more research is warranted.…”
Section: Adrenoceptors In Human Adipose Tissuementioning
confidence: 99%